Effect of apron length on jet-flipping scour downstream of a submerged weir - Tay, Kelvin Yu Jie (2017)
River channel downstream of a hydraulic structure is prone to local scouring which may undermines the stability of the structure. Various studies had been conducted to study the effects of scouring using different hydraulic parameters. The main objective of this project is to investigate the relationships between flow rate, tailwater depth and apron length and their effects on the maximum scour depth and the occurrence of jet flipping phenomenon for flow over a submerged weir. The results showed that two jet flipping flow patterns were observed namely a bed jet regime and a surface jet regime. The bed jet regime refers to the scouring phase whereby the jet flow is attached to the river bed, resulting in local scouring. The surface jet regime occurs when the jet flow is attached to the surface of the channel, resulting in backfilling to the previously scoured region. The results showed that jet flipping phenomenon may occur even in the absence of an apron length. Flow field is the flow current that is observed in the experiments and vortices is a main part of it. Upon hitting the channel bed, jet flow splits into two directions resulting in rotating currents in the opposite directions. This will affect the type of flow pattern observed. Three types of flow patterns were observed in this study namely bed jet regime, surface jet regime and jet flipping phenomenon. Jet flipping consist of alternating flow patterns between bed jet and surface jet regime. Scour depth severity is dependent on the type of flow patterns observed. The deepest scouring condition amongst all the flow patterns is formed when bed jet is the dominant flow pattern. On the other hand, when surface jet is the dominant flow pattern, the local scour depth is minimised.